DAMPAK LIBERALISASI PERDAGANGAN TERHADAP DAYA SAING BERAS INDONESIA DI PASAR DOMESTIK - Hendri Widonoto; Yuli Haryati (University of Jember, 2008)
Global Trade Liberalization want the openness of market and infinite effort opportunity ( borderles world) and also abolition of import cost import and other commerce resistance. One of governmental policy in input storey level is give the input subsidy of produce, protection and price control and also guarantee the availability of fertilize. Erratic input use efficiency in storey level of paddy’s farming still not yet been reached in an optimal fashion. Government policy applied during the time, do not pursue the paddy competitiveness in storey farming level, nor improve the added value meaning, because of from input and output exported only fertilize is just urea, so that protection and added value applied by a government not yet been felt by farmer. Rice supply in domestic market is bigger than demand, excess of stock rice of equal to 613.364 ton. Supply and demand of rice in domestic market by significant each influenced by paddy productivity and amount the resident with the elasticity of each 0,9 and 1,1. Keywords : Paddy commodity, Rice competitiveness, Domestic market .